Digitalizing Employment Social Security Services in Indonesia: A Literature-Based Study of the JMO Application by BPJS Ketenagakerjaan - Devi Dama Yanti Hutabarat; Ilfa Nadhira Afiqa; Najwa Ajrina; Naufal Fauzan Nasution; Habieb Pahlevi; M.L Sudarshana; Firman Karim; Nisha Marina (CV Media Inti Teknologi, 2025)
Background of Study : Digital transformation has reshaped public services in Indonesia, especially in social security. BPJS Ketenagakerjaan faces challenges like complex bureaucracy and limited access. The JMO app, launched in 2021, aims to address these issues by offering digital self-service features. Aims and Scope Paper : This study explores how digitalization improves public service access and satisfaction in BPJS Ketenagakerjaan. The focus includes service expansion, optimization of JMO features, and evaluation of digital service outcomes for participants. Methods: A qualitative literature review method was used. A total of 20 sources published between 2022 and 2025 were analyzed. Thematic analysis helped identify key trends and challenges in the digital implementation of BPJS Ketenagakerjaan services. Result: The findings show that JMO improves service access, transparency, and user satisfaction. It streamlines claims processing and reduces dependency on in-person visits. However, digital gaps remain, including limited literacy and technical issues for some users. Conclusion: The JMO application demonstrates the potential of digital transformation in public services. While improvements are evident, success depends on inclusive design, ongoing infrastructure support, and user education to ensure equal access for all participants.